Productos turísticos y oferta del cantón Pelileo, provincia de Tungurahua - Katherine Carolina, Agualongo López (2019)
The purpose of this research is to determine the relationship of tourism products with the offer of the Pelileo canton, province of Tungurahua. The research is qualitative and quantitative, a cross-sectional non-experimental study design, in which the survey instrument was used for the two study variables, Tourism Products (VI) and Offer (DV), as a sample was taken to tourists entering the Pelileo canton by the Independent Variable and the tourism service providers by the dependent variable. With the data obtained in the application of surveys, the general and specific hypotheses were checked using the SPSS program applying the correlation coefficient of Rho Spearman, which allowed determining the relationship of tourism products and their components with the canton offer Pelileo followed by the presentation of the surveys. Elements that allowed to direct a proposal that consists of a tourist product for the Pelileo canton in response to the research problem. The product consisted of the analysis of the current situation of the tourist activity and its factors, in addition the methodology for the design of the same was identified and the technical evaluation sheets of the tourist attractions that are part of the product were made. This proposal seeks to improve, innovate and adequately address the canton's offer in such a way that it responds to the needs of the demand and meets its expectations.